Seismic velocity changes caused by an overburden stress - Korneev, V.; Glubokovskikh, Stanislav (2013)
An increase in seismic velocity with depth is a common rock property, one that can be encountered practically everywhere. Overburden pressure increases vertical stress, producing a nonlinear elastic response. Application of a conventional nonlinear theory to this problem leads to transverse isotropy, with explicit relationships between nonlinear constants and elastic anisotropy parameters. These relationships can be used in velocity "depth trend" removal and in computing offset-dependent corrections for stacking and migration. Assumptions about small static stress and the use of linearized solutions for its evaluation are invalid for overburden problems - more accurate approximations are required. Realistic tomography models should account for elastic anisotropy as a basic feature. Our theory gives an accurate fit to well and stacking velocity data for the Los Angeles Basin. Overburden stress is a likely cause of shear-wave generation by underground explosions.